133 Although CT Coronary Angiography in the West of Scotland is Used in a Higher Risk Population than Recommended by Nice, The Rate of Subsequent Invasive Coronary Angiography is Lower than in the Promise and Scot-Heart Studies. (3rd June 2016) - Jackson, Alice M; Ftouni, Manwella; Philip, Elizabeth; Adams, Jacqueline; Byrne, John; Oldroyd, Keith; Good, Richard
Abstract : Background: NICE guidelines recommend CT coronary angiography (CTCA) as a first line investigation for patients with chest pain and an estimated likelihood of coronary artery disease (CAD) of 10–29%. These guidelines do not recommend exercise testing in this patient group. The recently published PROMISE and SCOT-HEART studies extended the use of CTCA to moderate and high risk patients. Neither study has shown clear clinical benefit for patient randomised to CTCA and there remains a divergence of opinion regarding the appropriateness of CTCA in these patient groups. In particular, there is a concern that CTCA may increase the number of future invasive coronary angiograms. We studied patients referred to the CTCA service in our centre and compared their predicted risk, prior stress testing and subsequent investigations to the NICE guidance and with data from the PROMISE and SCOT-Heart studies. Methods: Data was collected prospectively for consecutive patients undergoing CTCA over a 3 month period. CTCA reports were retrospectively reviewed with details recorded of the scan protocol, scan quality and severity of coronary disease. Our cardiac catheterisation database was retrospectively interrogated 6 months after the final patient underwent CTCA to document any subsequent invasive coronary angiography, PCI or CABG. Results: A total of 226 patients underwent CTCA during the 3 month study period (Table 1 ). The distribution of likelihood of CAD according the NICE guideline tables is shown in Figure 1 . Only 34/226 (15%) had a pre-test probability of having significant CAD within the 10–29% category. Prior to CTCA, 153 patients (68%) had exercise ECG testing with 12/226 (5%) undergoing stress perfusion imaging. Overall, 164/226 (73%) patients had normal arteries or minimal CAD with 52 (23%) patients reported to have moderate/severe disease (Figure 2). 21/226 (9.3%) patients subsequently underwent invasive coronary angiography. 5 of these patients had pressure wire assessment (PWS) of coronary lesions with one of these patients subsequently undergoing revascularisation by CABG. An additional 4 patients underwent percutaneous revascularisation without PWS. Conclusion: Only a minority of patients referred for CTCA to our centre were within the pre-test probability category recommended by NICE for this test. The majority of patients had undergone exercise testing prior to CTCA again suggesting limited adherence to the NICE guidelines. Despite the majority of patients having a pre-test probability > 30%, only 9.3% of patients underwent subsequent invasive angiography, less than in the patient group randomised to CTCA in both the PROMISE and SCOT-HEART studies (12%). Further studies are needed to better define the population that would most benefit from CTCA.